DEVELOPMENT OF ADOBE FLASH BASED LEARNING MEDIA TO TRAIN STUDENTS’ CRITICAL THINKING SKILL WITH TOPIC OF OPTICAL INSTRUMENT - Jane Koswojo; Sugimin Wahyu Winata; Wasis Wasis (Magister Scientiae, 2020)
This research employs a developmental research design with 4D model and tested on grade X senior high school students with one group as the subjects for the pretest and posttest. Learning media and supporting tools in this research, developed as a jigsaw-type cooperative learning model, were expected to be able to train students' critical thinking skills. The students' critical thinking skills improved as represented by the average N-gain score of 0.83 for replication I and 0.88 for replication II, and it was categorized as a high category. This research concluded that Adobe Flash-based physics learning media with the topic of "optical instrument" can be used to train students' critical thinking skill.